CRYSTAL CHEMISTRY OF HIGH-PRESSURE BASI4O9 IN THE TRIGONAL (P3) BARIUM TETRAGERMANATE STRUCTURE - Hazen R.M.; Yang H.; Finger L.W.; Fursenko B.A. (My University, 1999)
Crystals of BaSi4O9 synthesized at 4 GPa and 1000 degrees C were determined to be isostructural with barium tetragermanate [trigonal, space group P3, a = 11.2469(11) and c = 4.4851(6) Aa, V = 491.3(1) Aa 3 ]. The structure (R = 2.4%) features a corner-linked framework of three-member silicate tetrahedral rings, which are cross-linked by isolated silicate octahedra. Ba cations occupy tenfold-coordinated sites in channels defined by the silicate framework. This structure is 4.2% denser than the topologically similar benitoite form of high-pressure BaSi 4 O 9 , which was produced by grinding the barium tetragermanate-type crystals described in this report.